The construct Validity of the CES-D among HIV-Infected Perinatal Thai Women: Explanatory and Confirmatory Factor Analysis - Ratchneewan, Ross; Andrea, Warner Stidham; Pimpanitta, Saenyakul; Carolyn, Kleman (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
It is important to measure depressive symptoms in HIV-infected individuals because depressive symptoms have been found to be correlated with faster progression to AIDS. Worldwide, the CES-D has been used to assess depressive symptoms and examined for its construct validity. However, no previous studies have investigated the CES-D’s construct validity among HIV-infected perinatal women. Therefore, the objective of this study was to examine the construct validity of the CES-D using both explanatory and confirmatory factor analysis among HIV-positive perinatal women in Thailand. Results showed that, overall, the CES-D is a 4-factor instrument with good construct validity and can be used to evaluate depressive symptoms among HIV-positive perinatal Thai women. However, some items from our study loaded differently on the 4 factors from Radloff’s model. Finally, the CES-D can be used as a general-factor scale without being compromised.
Keywords: HIV; CES-D; Confirmatory factor analysis; Exploratory factor analysis; perinatal women; Thailand.